The Existence of Multicultural-Universal Education Values in Pesantren - Aisyah Abdul Jabbar; Meguellati Achour; Muhammad Badat Alauddin; Edwards Geraldine; Thufail Al Mutawakkil; Ishmah Afiyah; Jihan Husna Srifyan (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
Boarding schools have become distinctive educational institutions in Indonesia, playing an important role in shaping students' character, morals, and knowledge. This research paper is to discuss the values of multicultural and universal education reflected in boarding in Indonesia. Another objective of this study is to analyze the goals, methods, and outcomes of multicultural and universal education in the context of boarding schools. This research method involves collecting data from various primary and secondary sources, including academic literature, interviews with scholars, and direct observation in different boarding schools throughout Indonesia. Qualitative analysis is used to understand the multicultural and universal educational approach applied in boarding schools. The results showed that boarding schools in Indonesia have broad educational objectives, including the development of Islamic character, academic skills, and multicultural understanding. The educational methods used include classical religious learning, group discussions, and extracurricular activities that promote tolerance and cross-cultural cooperation. Boarding schools also emphasize universal values such as justice, equality, and unity, which are integrated into their curriculum. In conclusion, boarding schools in Indonesia have a significant role in promoting multicultural and universal education. Through the objectives, methods, and educational outcomes offered, boarding schools can form individuals who not only have solid religious knowledge but also have a strong understanding of cultural diversity and universal values that are important in a pluralistic society.